Comparative finite element modelling approaches for the seismic vulnerability analysis of historical masonry structures: the case study of the Cathedral of Catanzaro (Italy). (11th October 2022) - Gaetano, Daniele; Greco, Fabrizio; Leonetti, Lorenzo; Pascuzzo, Arturo; Skrame, Aurora
The vulnerability assessment of an ancient cathedral located in Southern Italy is performed by using both conventional and advanced finite element models. The structural safety under both static and seismic loading conditions, also including wind and temperature loadings, is mainly assessed via a response spectrum analysis performed on an accurate 3D global model of the cathedral ad hoc developed. Moreover, additional pushover analyses are conducted using an advanced nonlinear model, for a better understanding of the seismic behaviour of the analysed structure. In particular, an innovative diffuse cohesive interface approach has been adopted and suitably compared with a well-established damage model, also in terms of associated mesh dependency issues. Finally, a critical discussion of the numerical results obtained via all these different models is reported, with the aim of comparing their predictive capabilities in terms of both global and local structural safety.